2022
DOI: 10.1111/jcpe.13725
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory fibrous hyaluronic acid‐Fmoc‐diphenylalanine‐based hydrogel induces bone regeneration

Abstract: Aim: To investigate the potential of an ultrashort aromatic peptide hydrogelator integrated with hyaluronic acid (HA) to serve as a scaffold for bone regeneration.Materials and Methods: Fluorenylmethyloxycarbonyl-diphenylalanine (FmocFF)/HA hydrogel was prepared and characterized using microscopy and rheology. Osteogenic differentiation of MC3T3-E1 preosteoblasts was investigated using Alizarin red, alkaline phosphatase and calcium deposition assays. In vivo, 5-mm-diameter calvarial critical-sized defects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Calcium deposition in the mineralized extracellular matrix (ECM) is regarded as a phenotypic marker of osteoblast maturation and can be used to measure the osteoinductive ability of the above composites. 40 Alizarin red S (ARS) staining was performed to evaluate the formation of calcium nodules of osteoblasts cultured on different materials for 14 days. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium deposition in the mineralized extracellular matrix (ECM) is regarded as a phenotypic marker of osteoblast maturation and can be used to measure the osteoinductive ability of the above composites. 40 Alizarin red S (ARS) staining was performed to evaluate the formation of calcium nodules of osteoblasts cultured on different materials for 14 days. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study 19 Micro-CT was used to explore the advantages of an hydrogel-filled defects in rat model. The Micro-CT results indicated bone regeneration from the defect margins inwards, yet, bony islets were observed in the center of the defect (i.e., inner region).…”
Section: Discussionmentioning
confidence: 99%
“…67 However, nowadays, there is a significant shift in interest from the development of single component-based peptide-based biomaterials towards exploring biomolecular systems mimicking the complexity of the native extracellular matrix (ECM). 60,[68][69][70] In this direction, very few studies in the literature have shown the potential of simple non-covalent interactions between the ECM-inspired peptides and biopolymers towards the formation of scaffolds with diverse mechanical and biological properties. 17,42 However, the fundamental molecular processes leading to the formation of these supramolecular structures in biomolecular systems have not been discussed in the literature.…”
Section: Microscopic Evidence Of the Self-assembly Mechanismmentioning
confidence: 99%